Mediating role of inflammatory markers (NLR, PLR, SII, SIRI) in the association between 25(OH)D deficiency and obesity in children and adolescents - Yanchao Li; Xiaoshan Shao (Journal of Health, Population and Nutrition)
Abstract Background The association between vitamin D deficiency and obesity in children and adolescents has garnered significant attention; however, the underlying mechanisms remain unclear. It is hypothesized that the inflammatory response may mediate the relationship between vitamin D deficiency and obesity. Objective This study aims to investigate the mediating roles of inflammatory markers—namely, the neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR), systemic immune inflammation index (SII), and systemic inflammatory response index (SIRI)—in the association between 25(OH)D deficiency and obesity. Methods This study utilized data from the 2009–2018 National Health and Nutrition Examination Survey (NHANES) and included a sample of children and adolescents aged 2 to 17 years. The analysis employed complex sampling design weights, with continuous variables expressed as weighted means and categorical variables as weighted percentages. Baseline characteristics were compared using chi-square tests and t-tests. Inflammatory markers were categorized into quartiles, while the 25(OH)D levels were classified into three groups: deficiency, insufficiency, and adequacy. Multivariate logistic regression was conducted to examine the association between 25(OH)D deficiency, inflammatory markers, and obesity. Additionally, the mediating effect of inflammatory markers on the relationship between 25(OH)D deficiency and obesity was investigated through mediation analysis. Results A total of 10,613 children and adolescents were included in the study, with 1,650 classified in the obesity group. The findings indicated a significant association between 25(OH)D deficiency and obesity risk (OR = 0.634, 95% CI: 0.440–0.915, p = 0.018). Inflammatory markers, specifically NLR, PLR, SII, and SIRI, partially mediated the relationship between 25(OH)D deficiency and obesity, with NLR and SII exhibiting the most substantial mediating effects (mediation ratios of 3.85% and 4.29%, respectively, p < 0.001). Mediation analysis revealed that the total effect (TE), direct effect (DE), and indirect effect (IE) were all negative, suggesting that an increase in 25(OH)D levels is associated with a reduced risk of obesity, with inflammatory markers serving as intermediaries in this process. Conclusion This study demonstrates a significant association between 25(OH)D deficiency and obesity in children and adolescents, with inflammatory markers—particularly NLR and SII—playing a partial mediating role in this relationship. These findings indicate that 25(OH)D may influence the development of obesity by modulating the inflammatory response.